Photoactive Heteropore Covalent Metal–Organic Frameworks for CO2 Photoreduction - Xu Chen; Fangjie Xu; Yu-Yang Li; Shu-Ya Guo; Ji Zheng; Li-Yang Chen; Zhi-Hong Lin; Kun Wu; Bingzhe Wang; Guo-Hong Ning; Dan Li (Journal of the American Chemical Society, 2026)
Abstract Metal–organic frameworks (MOFs) as a class of promising photocatalysts have been used for photocatalytic CO2 reduction reaction (CO2RR). Although many strategies have been developed for enhancing the photocatalytic activities, constructing photoactive heteropore MOFs for CO2RR remains largely unexplored. Herein, we report the synthesis of two two-dimensional (2D) copper cyclic trinuclear unit (Cu-CTU)-based heteropore covalent MOFs (CMOFs) and two homopore analogues. Interestingly, the heteropore CMOFs showed two times higher CO2 uptake than their homopore analogues. Moreover, the introduction of photosensitive units into heteropore CMOFs promoted light harvesting as well as charge separation, achieving a CO generation rate of 3548 μmol g–1 h–1 with 94.7% selectivity and an apparent quantum yield (AQY) of 6.78% at 420 nm in the presence of [Ru(bpy)3]Cl2. Notably, the photoactive heteropore CMOFs delivered high photocatalytic activity under diluted CO2 and natural sunlight conditions. Our work demonstrated that incorporation of heteropore structures and photosensitive units into MOFs can synergistically enhance photocatalytic CO2RR performance.